Thermal performance of a boiling-driven heat spreader using passive flow control - Lim, Hyunmuk; Doh, Su Yoon; Shin, Dong Hwan; You, Seung M.; Lee, Jungho (Case Studies in Thermal Engineering, 2023)
This study investigates a wickless two-phase heat spreader with boiling heat transfer (boiling-driven heat spreaders) for the thermal management of hot spots with a high heat flux of more than 200 W/cm2. Thermal management studies are performed using two different approaches. First, a boiling-driven heat spreader is fabricated to confirm the thermal performance according to the heat flux, orientation, and internal support design. Second, the working mechanism of the heat spreader is established for a visualization test sample (90 × 90 mm2, inner gap of 1 mm), along with the high-speed in-situ visualization of the boiling/condensation phenomena. It is essential to understand the working mechanism of the heat spreader for improving its thermal performance. Consequently, we propose a new advanced boiling-driven heat spreader with improved thermal performance using a passive flow control design. The internal supports provide a bubble escape passage with different pressure drop characteristics. As a result, the thermal performance of the advanced boiling-driven heat spreader is independent of the orientation up to a heat flux of 200 W/cm2, and the thermal resistance is less than 0.17 K/W. Hence, the advanced heat spreader is suitable for dissipating highly concentrated heat in various thermal management applications.
Keywords: Boiling heat transfer; Boiling-driven heat spreader; Heat spreaders; High heat flux; Hotspots; Internal supports; Passive flow control; Thermal Performance; Two-phase heat spreader; Working mechanisms; Boiling-driven heat spreader; Passive flow control; Thermal resistances; Visualization